Anesthesia in pediatric dentistry - V. V. Lazarev; D. M. Haliullin (Вестник анестезиологии и реаниматологии, 2019)
The review was carried out using the medical databases PubMed, Scopus, The Cochrane Library, CyberLeninka.The objective: evaluate the range of methods used for anesthesia in dentistry in children. Results. Inhalation anesthesia is most commonly used with halogenated volatile anesthetics, in combination with local or intravenous anesthesia. Xenon is a perspective inhalation anesthetic for general anesthesia in dentistry. However, information its use in children is limited.